Characterization of Essential Oils from Different Taxa Belonging to the Genus Teucrium in Sardinia Island, Italy - Alfredo Maccioni; Danilo Falconieri; Cinzia Sanna; Silvia Porcedda; Alessandra Piras; Andrea Maxia (Plants, 2021)
The genus Teucrium L. (Lamiaceae) is a genus growing in mild climate zones, particularly in the Mediterranean Basin and Central Asia. It is represented by 11 taxa in Sardinia (Italy), living commonly in sunny habitats. In this study, the following eight Sardinian Teucrium taxa were selected, and the essential oils (EOs), obtained by stem distillation, were analyzed by GC–FID and GC–MS: T. capitatum subsp. capitatum, T. chamaedrys subsp. chamaedrys, T. flavum subsp. glaucum, T. marum, T. massiliense, T. scordium subsp. scordioides, T. scorodonia, and T. subspinosum. The comprehensive analyses led to the identification of 87 constituents representing the majority of the volatile compounds. Significant differences, both qualitative and quantitative, were observed between the taxa. Overall, monoterpenes and sesquiterpenes characterized all Teucrium EOs: T. capitatum subsp. capitatum and T. flavum subsp. glaucum revealed the highest content of monoterpene hydrocarbons, while in the other Teucrium taxa sesquiterpene hydrocarbons prevailed. Worthy of note, diterpenes were found only in T. marum and T. subspinosum, whereas T. massiliense was rich in non-terpenic oxygenated compounds. To the best of our knowledge, this is the first comprehensive report on the chemical composition of EOs obtained from Sardinian Teucrium species.